Protective effects of coconut water against the intraperitoneal infused carbon tetrachloride-induced toxicity—evaluations of biochemical, haematological and histopathological profiles in rats - Emmanuel, Okezie (2023)
Body weight of 14 days treatment of coconut water on CCl4-induced toxicity Figure 1 represents the protective effect of coconut water on body weight of CCl4-induced toxicity in both male and female rats. No significant changes (p > 0.05) in body weight were observed in both sexes in all the treatment groups.